Self-reported hypoglycemia in insulin-treated patients with diabetes: Results from an international survey on 7289 patients from nine countries. (December 2017) - Emral, Rifat; Pathan, Faruque; Cortés, Carlos Augusto Yepes; El-Hefnawy, M. Hesham; Goh, Su-Yen; Gómez, Ana Maria; Murphy, Angela; Abusnana, Salah; Rudijanto, Achmad; Jain, Anand; Ma, Zhulin; Mirasol, Roberto; et al.
Highlights: The study assessed hypoglycemia incidence in insulin-treated patients with diabetes. Prospectively, hypoglycemia was reported by over 95% of patients. Hypoglycemia rates vary according to treatment regimen. Estimated rates show hypoglycemia is under-reported and therefore under-estimated. Patient response to hypoglycemia impacts productivity and healthcare utilization. Abstract: Aims: Hypoglycemia constitutes a significant barrier to achieving glycemic control with insulin in both type 1 and type 2 diabetes. Historically, it has been difficult to accurately verify the rates of hypoglycemia within a clinical setting and there is a need for high-quality, real-world data to ascertain the true rates of hypoglycemia in clinical practice. The global Hypoglycemia Assessment Tool (HAT) study was designed to assess the global incidence of hypoglycemia in patients with insulin-treated diabetes, and the results have indicated that the overall incidence of hypoglycemia is high, with large variations between geographical regions. Methods: The International Operations HAT (IO HAT) study retrospectively and prospectively assessed the incidence of hypoglycemia in patients with insulin-treated diabetes in Bangladesh, Colombia, Egypt, Indonesia, Philippines, Singapore, South Africa, Turkey, and United Arab Emirates. Results: During the prospective period, hypoglycemic events were reported by 97.4% of patients with type 1 diabetes and 95.3% of those with type 2 diabetes, with an estimated rate of 6.86 events per patient per month (PPPM) for patients with type 1 diabetes and 2.37 events PPPM for patients with type 2 diabetes. Conclusions: These results represent the first patient-reported dataset on hypoglycemia in the participating countries and confirm that hypoglycemia is under-reported and more widespread than previously believed. Although the incidence of hypoglycemia was variable among patients on different treatment regimens, there were substantial impacts on both productivity and healthcare utilization following an episode of hypoglycemia. This trial is registered at clinicaltrials.gov:NCT02306681.